Shimmering images trans cinema, embodiment, and the aesthetics of change - Steinbock, Eliza 1980- (Duke University Press, 2019)
In Shimmering Images Eliza Steinbock traces how cinema offers alternative ways to understand gender transitions through a specific aesthetics of change. Drawing on Barthes's idea of the "shimmer" and Foucault's notion of sex as a mirage, the author shows how sex and gender can appear mirage-like on film, an effect they label shimmering. Steinbock applies the concept of shimmering-which delineates change in its emergent form as well as the qualities of transforming bodies, images, and affects-to analyses of films that span time and genre. These include examinations of the fantastic and phantasmagorical shimmerings of sex change in Georges Méliès's nineteenth-century trick films and Lili Elbe's 1931 autobiographical writings and photomontage in Man into Woman. Steinbock also explores more recent documentaries, science fiction, and pornographic and experimental films. Presenting a cinematic philosophy of transgender embodiment that demonstrates how shimmering images mediate transitioning, Steinbock not only offers a corrective to the gender binary orientation of feminist film theory; they open up new means to understand trans ontologies and epistemologies as emergent, affective, and processual